2013
DOI: 10.1136/bmjopen-2013-002616
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical results after cataract surgery with and without capsular tension ring in patients with retinitis pigmentosa: a retrospective study

Abstract: ObjectivesTo describe the long-term clinical outcomes after cataract surgery with and without capsular tension ring (CTR) in a group of patients with retinitis pigmentosa (RP).DesignA retrospective study.SettingTertiary referral centre.Participants52 eyes (46 patients) with RP.InterventionsCataract surgery was undertaken between October 2002 and May 2010.Primary and secondary outcome measuresVisual acuity, secondary cataract, capsular contraction syndrome (CCS), intraocular pressure, cystoid macular edema (CME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 20 publications
1
34
3
5
Order By: Relevance
“…Celik et al [ 93 ] indicated that RP with zonular weakness is one of the indications for CTR implantation. In the study of Bayyoud et al [ 13 ], they demonstrated RP eyes under phacoemulsification and IOL implantation with CTRs showed less long-term postoperative complications, such as PCO (23/52, 44%), capsular phimosis (2/52, 4%), and improved visual acuity at a mean follow-up time of 26 months. Conversely, some reported cases still exhibit late-onset subluxation or dislocation of IOL or CTR-IOL-capsular bag complex, perhaps indicating the insufficient strength of standard CTR to support a profound zonular weakness [ 67 , 96 ].…”
Section: Cataract Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Celik et al [ 93 ] indicated that RP with zonular weakness is one of the indications for CTR implantation. In the study of Bayyoud et al [ 13 ], they demonstrated RP eyes under phacoemulsification and IOL implantation with CTRs showed less long-term postoperative complications, such as PCO (23/52, 44%), capsular phimosis (2/52, 4%), and improved visual acuity at a mean follow-up time of 26 months. Conversely, some reported cases still exhibit late-onset subluxation or dislocation of IOL or CTR-IOL-capsular bag complex, perhaps indicating the insufficient strength of standard CTR to support a profound zonular weakness [ 67 , 96 ].…”
Section: Cataract Extractionmentioning
confidence: 99%
“…Based on the constrict visual field, loss of transparency in the eyes with RP only in a small part of the lens can lead to disproportionate visual acuity reduction [ 7 ]. Furthermore, compared with the mean age at surgery of 72–74 years for age-related cataract (ARC) [ 8 ], the surgery time in RP is earlier, with an average age at surgery of 47–63 years old in previous studies [ 6 , 8 13 ] and 83% of the patients with mean age at surgery between 30 and 59 years in the study of Bastek et al [ 14 ]. The decreased visual acuity with continuous development of cataracts severely influences the patient's life quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general guideline, cataract surgery is indicated in individuals with lens opacities and should be performed as soon as it causes significant impairment of vision and before the disease evolves to a point at which it could limit postoperative recovery. In general, RP patients experience significant improvements in visual acuity after cataract surgery (reviewed in Bayyoud et al 2013;Dikopf et al 2013). However, patients should be informed that postoperative visual acuity cannot be accurately predicted before surgery because the part of cataract versus the part of macular dysfunction in the decrease of vision is sometime difficult to evaluate.…”
Section: Current Therapies For Inherited Retinal Diseases General Recmentioning
confidence: 99%
“…By comparison, aggressive capsularphimosis, zonular weakness and IOL dislocation have all been reported in retinitis pigmentosa. 13,[17][18][19][20][21][22][23] Phototoxicity is a serious consideration in the context of attenuated photoreceptor and RPE function as seen in choroideremia. The main risk factor for phototoxicity is the duration of surgery, 24,25 which was kept to a minimum in all the patients and the eye was shielded from the microscope light during the pauses in operating.…”
Section: Eyementioning
confidence: 99%